Role of Interpersonal Relationships in Mothers' Foods Choice Decisions for Children Ages 1 < 5 Years in Rural Mexico (P10-051-19). (13th June 2019) - Reyes, Ligia; Frongillo, Edward; Blake, Christine; Moore, Spencer; Gonzalez, Wendy; Bonvecchio, Anabelle
Abstract: Objectives: To understand how mothers' interpersonal relationships influence food choice decisions they make to feed children ages 1 to <5 years old in rural Mexico. Methods: Semi-structured interviews were conducted with 46 mothers from 3 rural communities in Mexico in November and December 2016. Mothers were asked about their daily activities, their own knowledge about child feeding, the social ties from which they obtain information about child feeding, and local normative beliefs about food. Interviews were audio-recorded, transcribed verbatim, and analyzed using the constant comparative method. Thematic coding was used to identify the underlying values and meanings mothers ascribed to foods and the influential figures in their social circle to understand how interpersonal relationships influenced child feeding decisions. Results: Most mothers had no formal employment and spent their day in activities such as upkeep of home, caring for their children, getting food, preparing meals, looking after their animals, and harvesting. Most mothers lived in multigenerational households or near relatives. Mothers' knowledge about child feeding had a foundation in practices from their own mothers, being child caregivers to their siblings, employment as child caregivers in urban settings, and having older children. Mothers had prominent figures who influenced their decisions about child feeding. These figures were older women living in the household, other mothers within their social circle, health and social program personnel, children's fathers, and children themselves. Mothers described specific foods and preparations locally acceptable to feed to children, noting that some beliefs and practices might conflict with others. In making decisions about what to feed their children, mothers appraised who their social ties were and their feeding practices. For example, mothers took in information from other mothers based on their perception of whether the child was well-fed, which included child appearance. Conclusions: Mothers' interpersonal relationships played an important role in their child feeding decisions. When designing a program to improve food choice, identifying and accounting for mothers' key social ties regarding child feeding could enhance positive behavior change. Funding Sources: SPARC Graduate Research Grant from University of South Carolina.